Integrating microbial metagenomics and physicochemical parameters and a new perspective on starter culture for fine cocoa fermentation. (February 2021) - de C. Lima, Carolina O.; Vaz, Aline B.M.; De Castro, Giovanni M.; Lobo, Francisco; Solar, Ricardo; Rodrigues, Cristine; Martins Pinto, Luiz Roberto; Vandenberghe, Luciana; Pereira, Gilberto; Miúra da Costa, Andréa; Benevides, Raquel Guimarães; Azevedo, Vasco; et al.
Abstract: Cocoa beans used for chocolate production are fermented seeds of Theobroma cacao obtained by a natural fermentation process. The flavors and chemical compounds produced during the fermentation process make this step one of the most important in fine chocolate production. Herein, an integrative analysis of the variation of microbial community structure, using a shotgun metagenomics approach and associated physicochemical features, was performed during fermentation of fine cocoa beans. Samples of Forastero variety (FOR) and a mixture of two hybrids (PS1319 and CCN51) (MIX) from Bahia, Brazil, were analyzed at 7 different times. In the beginning (0 h), the structures of microbial communities were very different between FOR and MIX, reflecting the original plant-associated microbiomes. The highest change in microbial community structures occurred at the first 24 h of fermentation, with a marked increase in temperature and acetic acid concentration, and pH decrease. At 24–48 h both microbial community structures were quite homogenous regarding temperature, acetic acid, succinic acid, pH, soluble proteins and total phenols. During 72–96 h, the community structure resembles an acidic and warmer environment, prevailing few acetic acid bacteria. Taxonomic richness and abundance at 72–144 h exhibited significant correlation with temperature, reducing sugars, succinic, and acetic acids. Finally, we recommend that dominant microbial species of spontaneous fine cocoa fermentations should be considered as inoculum in accordance with the farm/region and GMP to maintain a differential organoleptic feature for production of fine chocolate. In our study, a starter inoculum composed of Acetobacter pausterianus and Hanseniaspora opuntiae strains is indicated. Highlights: 14 samples of fine cocoa beans from Brazil were analyzed by shotgun metagenomics. Microbiome of pulp and physicochemical of fine cocoa beans (chocolate) were studied. Temperature and organic acids had a high influence during all fermentation. Hanseniaspora and AAB were dominant; LAB were not important for cocoa fermentation. Microbial inoculum for fine chocolate production: consider the farm/region and GMP.